The Role of Local Champion In Community - Based Adaptation In Semarang Coastal Area - Septiarani, Bintang; Handayani, Wiwandari (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2016)
Community-based adaptation (CBA) is a new approach that is attractive because it is a process of planning led by the community, based on community priorities, needs, knowledge and capacity - a process that should empower people to plan for climate change impacts (Hordijk and baud, 2010). Governance at the community level regarded to be a way to help them in adapting and maintain their livelihood on the coastal so that they can remain in the region. Governance in community engaged individual communities to group and jointly manages their livelihoods and conservation in their coastal areas. The intervention of the government and non-government organizations also play a role in the process of adaptation that occurs. This paper aim to elaborate the role of local champion in CBA process. Interesting findings from Tapak Village, Semarang who have done their community-based adaptation process is that the involvement of the community in the adaptation to climate change is greatly influenced by the presence of local champion in the region. The existence of networks between community and the relevant stakeholders in both the government and non-government organizations also became one of the supporting factors for the sustainability of community-based adaptation processes in coastal areas of Semarang City.